Experimental study of the effect of top-ring clearance volume on unburned hydrocarbon concentrations - Özkan, M; Deniz, O; Sandalci, T (INDERSCIENCE ENTERPRISES LTD, 2002)
The clearance volume between the piston, the cylinder and the top compression ring in an internal combustion engine has a significant effect on the unburned hydrocarbon concentration. The high heat transfer from the burning mixture to the cylinder surface extinguishes the flame front, and this is the main reason for increased unburned hydrocarbon concentrations. The heat transfer between the mixture and the clearance volume surface is affected by the ratio of coolant surface to the clearance volume. In this study the effect of the ratio of the coolant surface to the clearance volume on the unburned hydrocarbon concentration was investigated using three different purpose-built pistons. A decrease of this ratio reduced the unburned hydrocarbon concentration by 40%.
Keywords: clearance volume; flame front; unburned hydrocarbons; Environmental Sciences & Ecology